Autophagy in Pancreatic Cancer. (16th January 2012) - Grasso, Daniel; Garcia, Maria Noé; Iovanna, Juan L.
Abstract : Pancreatic adenocarcinoma (PDAC) is a devastating disease with an extremely poor life expectancy and no effective treatment. Autophagy is a process of degradation of cytoplasmic component capable of recycling cellular components or eliminate specific targets. The presence of autophagy in PDAC has been demonstrated. However, the implicated cellular pathways are not fully understood and, more importantly, the role of autophagy in PDAC is matter of intensive debate. This review summarizes recently published data in an attempt to clarify the importance of autophagy in this disease and try to reconcile apparently contradictory results.